Review of Islamic Law on the “Gandeng” System at Arisan with Arisan Menurun Model Via Online - Wahyudi, Muhamad; Rachmawati, Novia; El Muna, Naily (Et-Tijarie, 2024)
Arisan menurun “gandeng” system is an arisan where members of the voters of the initial sequence number are required to cooperate with the lower or last sequence number. This study discusses the review of Islamic law on the application of the joint system in social gatherings with a declining model via online.This type of research uses qualitative research that is descriptive in nature analysis; by using the field research method, the researcher is directly involved with the arisan admin and its participants. The research approach uses sociological juridical methods. The data sources used are primary and secondary data sources, while the data collection uses interview, documentation, and observation methods.The results of this study conclude that the implementation of the joint system in arisan with a menurun model via online on the @arisan. sukses.squad Instagram account, based on Islamic law, the pillars of qarḍ are valid but do not meet the requirements of qarḍ because the implementation of qarḍ in arisan decreases this joint system there is a taking of benefits, namely profits obtained from overpayment of arisan. This is not in accordance with Islamic Law, which is included in the element of ribā qarḍ, while the cost of fines is ribā jāhiliyah. The addition can be said to be ribā, and ribā is forbidden in Islamic law. The results of this study illustrate the implication that the implementation of this online arisn is permissible if the principle is carried out in a helping manner (ta'awun) as stated by Allah SWT in Surah Al-Maidah (5) verse 2.